Snowball Throwing Instructional Model: Middle School Students’ Learning Interest in Islamic Education - Mutmainah, Siti; Makbuloh, Deden; Saputra, M. Indra (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study intends to determine the effect of the snowball-throwing learning model on students' learning interest in Islamic religious education at the middle school level. The initial problem was low student interest and attention due to monotonous learning methods. This research employed a quantitative approach with a post-test-only control group type of quasi-experimental design. The method of sampling involved one experimental class using the Snowball Throwing model and one control class using conventional methods at Middle School 1 Waway Karya. The instrument used was a learning interest questionnaire that had been tested for validity and reliability. Data analysis was conducted through normality tests, homogeneity tests, and t-tests. The results indicated that the data were normally distributed and homogeneous. The t-test yielded a significance value of 0.008, which is less than 0.05 (p < 0.05), indicating a significant difference in learning interest between the two groups. Students who learned using the snowball-throwing model had a higher learning interest compared to students who learned with conventional methods. The activity of making and throwing questions in the form of paper balls was proven to be able to increase students' interest and attention in learning. The contribution of this research is to offer the snowball throwing model as an effective alternative learning strategy to increase students' learning interest in Islamic religious education subjects.